Collective mindsets: how to analyze neoliberal thinking - Pohlmann, Markus; Bär, Stefan; Valarini, Elizângela (Global economic elites and the new spirit of capitalism, 2024)
In analyzing societies, cultures or economies, collective mindsets play an important role. They tell us about the spiritual construction and the knowledge stocks of a given society, culture or economy, how this knowledge stock is translated into action orientations, how these orientations change over time and how different they are in various cultures.
Gesehen am 03.06.2024